Perceived importance of ICT in learning English: view from the Orang Asli students / Nur Alyani Khairol Anuar - Khairol Anuar, Nur Alyani (2012)
Technology has become important and marks its existence in almost everyone lives. With the rapid changes in the world of technologies and the enhanced use of ICT in our everyday lives, it is not surprising when the use of ICT in education has captured the attention of the educators and the world. Previous studies have shown that ICT bring positive effects on the students’ achievement. Lots of studies have their focus on the ICT integration in the education of students from rural community. Limited studies are found on the ICT in the education of Orang Asli population. This study intended to fill in the gap by focusing on the view of Orang Asli students toward the importance of ICT in learning English. 100 Orang Asli students from three districts in Pahang were involved. Quantitative approach were employed with questionnaires were used as the instrument. Findings revealed that Orang Asli students have low ICT competence with male students were recorded to have higher ICT competence than female. Despite the low ICT competence, Orang Asli students have positive attitude and showed no significance difference in gender. It is also clear that the level of ICT use in English classroom is low and. As for the preferred ICT related activities, majority of Orang Asli students preferred to have Internet-related activities in English classroom.